Weaving. Methods and tools against homelessness between anthropology and design - Valentina Porcellana (Antropologia, 2020)
Starting from our long experience in a participatory laboratory conducted by means of design and anthropology, we reflect on the contribution of creative and practical activities to the creation of collaborative communities of practice. The lab involves homeless people, researchers, university students, educators, and artists in the crafting of different artefacts. By describing the processes behind the creation of the artefacts, we will examine which kind of objects are produced, and the forms of community generated through a collaborative way of making. The objects, that are not allowed into the economic circuit, allow us to reflect on participatory practices beyond the competitive modes that prevail in the market. The laboratory – which is part of the day care services for homeless adults of the Municipality of Turin – has become a space of freedom and experimentation, despite the increasing bureaucratisation of the social services system. The laboratory is also an experiment in “creative re- sistance”, in which all participants can craft beauty.